Production of defects in ZBLAN, ZBLAN : Tm3+ and ZBLAN : Cr3+ glasses by ultra-short pulses laser interaction - Courrol, Lilia C.; Messaddeq, Younes [UNESP]; Messaddeq, Sandra H.; Ribeiro, Sidney José Lima [UNESP]; Samad, Ricardo E.; de Freitas, Anderson Z.; Vieira, Nilson D. (Pergamon-Elsevier B.V. Ltd, 2008)
In this work we have studied pure and thulium- and chromium-doped ZBLAN glasses irradiated by ultra-short laser pulses. A Ti:sapphire CPA system was used, producing a 500 Hz train of pulses, centered at 830 nm, with 375 mu J of energy and 50 fs of duration (FWHM). The beam was focused by a 20 Him lens, producing a converging beam with a waist of 12 pin. The absorption spectra before and after laser irradiation were obtained showing production of color centers in pure, thulium-doped and chromium-doped ZBLAN glasses. A damage threshold of 9.56 TW/cm(2) was determined for ZBLAN. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: glasses; colour centres; optical properties; radiation damage